Eksplorasi Pengalaman Konsumen terhadap Peran Online Customer Review dan Citra Merek terhadap Keputusan Pembelian Kosmetik pada Aplikasi Sociolla - Salwa Najah Huriyah; Atty Erdiana (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
The development of information technology and e-commerce has changed consumer behavior, especially in the cosmetics industry. Platforms like Sociolla are the main choice for consumers to buy cosmetic products online. This research explores the influence of online customer reviews and brand image on cosmetic purchasing decisions on the e-commerce platform. Customer reviews, both positive and negative, serve as an important reference that influences consumer perceptions of brand quality and credibility. On the other hand, a strong brand image can strengthen purchasing decisions by creating a sense of trust and emotional attachment. Using a qualitative approach, this research explores consumers' subjective experiences to understand the role of online reviews and brand image in purchasing decisions. The research findings are expected to provide deeper insight into the dynamics of consumer behavior in the Indonesian cosmetics e-commerce ecosystem.